POLICE DISCRETION IN HANDLING DEMONSTRATIONS AS SEEN IN THE APPLICATION OF HUMAN RIGHTS - Rahmad Masturi; A. Afgan Nugraha; Mujibur Rahman; Demas Candra Maheswara (PT. Radja Intercontinental Publishing, 2026)
Police discretion is the authority held by the Indonesian National Police (Polri) to act based on their own judgment in certain situations, including in handling demonstrations. However, in practice, the use of discretion often raises legal issues, particularly regarding potential human rights violations. This study aims to analyze the regulation of police discretion in handling demonstrations and assess whether existing restrictions are adequate to guarantee human rights protection. The research method used is normative legal research, with a statutory and conceptual approach. The legal materials used include primary legal materials in the form of laws and regulations related to the police and human rights, as well as secondary legal materials in the form of literature and expert opinions. The analysis was conducted qualitatively using a deductive method. The results indicate that, normatively, police discretion has a legal basis and limitations based on the principles of legality, proportionality, and accountability. However, the existing regulations are still general and open to multiple interpretations, potentially leading to abuse of authority and human rights violations in the practice of handling demonstrations. Therefore, a more assertive and measurable reformulation of police discretionary regulations is needed, establishing clear boundaries and developing standard operating procedures (SOPs) oriented toward protecting human rights. In conclusion, strengthening police discretionary regulations through clear limitations and implementing human rights-based SOPs is a crucial step toward achieving just, proportional law enforcement that respects citizens' rights to express their opinions in public.